Implementation of Interactive Learning Methods to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 100709 Aek Pining - Harahap, Karlinda; Bone, Dahraini (Journal of Indonesian Primary School, 2024)
Islamic Religious Education learning plays an important role in shaping the character of students from an early age. One of the main materials in grade 3 of elementary school is Becoming a Good and Polite Child, which aims to instill noble moral values. However, in practice, obstacles are still found such as low student participation and lack of understanding of the material. This study aims to analyze the effectiveness of interactive methods in improving learning of the material in grade 3 of SDN No. 100709 Aek Pining. The research method used is a qualitative approach with observation, interview, and documentation techniques. The results of the study showed that the application of interactive methods, such as group discussions, educational games, and role simulations, were able to increase student involvement in learning. Students became more active, enthusiastic, and understood the concept better. In addition, social interaction between students also increased, helping them to apply politeness and kindness in everyday life. Teachers also find it easier to convey material with a fun and non-monotonous approach. Thus, the application of interactive methods can be an effective strategy in improving the quality of Islamic Religious Education learning, especially in shaping children's good and polite characters. It is hoped that this method can be applied more widely to improve the effectiveness of learning in elementary schools.